The Survival of Interactional Sociolinguistics in the 21st Century - Irimiea, Silvia Blanca (European Journal of Multidisciplinary Studies, 2018)
Paradigm changes have occurred in all disciplines and fields of study all the time. The range of variability or change which affected major research areas has also triggered changes in the linguistic research of humanities studies. In the 21st century the pace at which new paradigmatic changes or turns appear has accelerated, with the result that, currently, researchers cannot confine their work to a single approach but need to position themselves simultaneously in relation to a variety of older and more recent turns. Amid these shifts, the present study looks at interactional sociolinguistics and its survival in the 21st century and highlights the reasons why it has given way to other sub-branches of linguistics. Equally, the study seeks to anticipate the possible future of interactional sociolinguistics.